Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1063/1.2363192
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally mediated photodissociation of ammonia: The influence of N–H stretching vibrations on passage through conical intersections

Abstract: Velocity map ion imaging of the H atoms formed in the photodissociation of vibrationally excited ammonia molecules measures the extent of adiabatic and nonadiabatic dissociation for different vibrations in the electronically excited state. Decomposition of molecules with an excited symmetric N-H stretch produces primarily ground state NH(2) along with a H atom. The kinetic energy release distribution is qualitatively similar to the ones from dissociation of ammonia excited to the electronic origin or to severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
101
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 27 publications
8
101
0
Order By: Relevance
“…The N = K a rotational states are labeled as red and green dots for ν 2 = 0 and 1, respectively. 18 Biesner et al, 14 Hause et al, 23 and Rodríguez et al, 26 at the total energy of 6.55 eV (the 0 0 state). (b) Comparison of the calculated H-translational energy distribution of the NH 2 (X̃2B 1 ) product with the experimental results of Biesner et al 14 and Rodríguez et al 26 at the total energy of 6.66 eV (the 2 1 state).…”
Section: * S Supporting Informationmentioning
confidence: 97%
“…The N = K a rotational states are labeled as red and green dots for ν 2 = 0 and 1, respectively. 18 Biesner et al, 14 Hause et al, 23 and Rodríguez et al, 26 at the total energy of 6.55 eV (the 0 0 state). (b) Comparison of the calculated H-translational energy distribution of the NH 2 (X̃2B 1 ) product with the experimental results of Biesner et al 14 and Rodríguez et al 26 at the total energy of 6.66 eV (the 2 1 state).…”
Section: * S Supporting Informationmentioning
confidence: 97%
“…There is a growing body of experiments and calculations on molecules with conical intersections in which the influence of one or more conical intersections on internal conversion or decomposition pathways is apparent [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. We have demonstrated that vibrational excitation can alter the probability of a molecule passing through a conical intersection by changing the trajectory that carries the system into the intersection [20,21]. In general, preparing molecules in a selected vibrational state prior to electronic excitation can alter dissociation dynamics and pathways by allowing the photoexcitation step to reach normally inaccessible regions of the excited-state potential.…”
Section: Introductionmentioning
confidence: 99%
“…The photolysis of ammonia is a prototypical example of dissociation through a conical intersection between two electronic states, and its study has shaped many ideas about the dissociation involving a conical intersection [20][21][22][23][24][25][26][27][28][29]. The adiabatic decomposition of electronically excited NH 3 (Ã 1 A 00 2 ) produces a hydrogen atom and an electronically excited fragment NH Ã 2 (H þ NH 2 ( 2 A 1 )), and the nonadiabatic decomposition *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success in this triatomic prototype spurred additional experiments on four atom molecules, including isocyanic acid, HNCO, 21 acetylene, C 2 H 2 , and its deuterated isotopologue, C 2 HD, 22 and ammonia, NH 3 , and its single deutarated variants, NHD 2 and NH 2 D. 23,24 An even larger a) Electronic mail: ibar@bgu.ac.il.…”
mentioning
confidence: 99%